2004
DOI: 10.1128/aem.70.9.5132-5137.2004
|View full text |Cite
|
Sign up to set email alerts
|

Clonality and Diversity of the Fish Pathogen Lactococcus garvieae in Mediterranean Countries

Abstract: Infection with Lactococcus garvieae is considered the most important risk factor for the European trout industry, and the losses are approximately 50% of the total production. To improve our understanding of the genetic links among strains originating from different countries, we examined the population structure of L. garvieae by comparing 81 strains isolated from different sources and ecosystems (41 farms in six countries) in which the bacterium is commonly found. Genetic similarities (as assessed with molec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
86
0
1

Year Published

2008
2008
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 75 publications
(90 citation statements)
references
References 24 publications
3
86
0
1
Order By: Relevance
“…In general, the highly clonal nature of Yersinia ruckeri isolates responsible for ERM in rainbow trout, as shown by this and other studies (Pyle et al 1987, Davies 1991a, Garcia et al 1998, is similar to that observed for other significant bacterial pathogens of farmed fish (Grayson et al 1999, Eyngor et al 2004, Reid et al 2004, Nash et al 2006. Although the isolates analysed were geographically biased and, in many cases, nonrandomly selected (e.g.…”
Section: Discussionsupporting
confidence: 67%
“…In general, the highly clonal nature of Yersinia ruckeri isolates responsible for ERM in rainbow trout, as shown by this and other studies (Pyle et al 1987, Davies 1991a, Garcia et al 1998, is similar to that observed for other significant bacterial pathogens of farmed fish (Grayson et al 1999, Eyngor et al 2004, Reid et al 2004, Nash et al 2006. Although the isolates analysed were geographically biased and, in many cases, nonrandomly selected (e.g.…”
Section: Discussionsupporting
confidence: 67%
“…In contrast, the bacterial strains isolated from raw milk, cheese and bovine mastitis show a quite heterogeneous distribution of the subtracted sequences which makes them difficult to classify in a clearly defined gene profile. The fact that genetic homogeneity of this pathogen exists in certain geographical areas or hosts where the disease is endemic has been proposed to be due to a clonal evolution of the bacterial population in such circumstances (Eyngor et al, 2004). In contrast, no evolutionary process would have taken place in hosts or geographical areas where the presence of L. garvieae is sporadic, leading to the maintenance of a genetic diversity of the pathogen (Eyngor et al, 2004).…”
Section: Discussionmentioning
confidence: 99%
“…The fact that genetic homogeneity of this pathogen exists in certain geographical areas or hosts where the disease is endemic has been proposed to be due to a clonal evolution of the bacterial population in such circumstances (Eyngor et al, 2004). In contrast, no evolutionary process would have taken place in hosts or geographical areas where the presence of L. garvieae is sporadic, leading to the maintenance of a genetic diversity of the pathogen (Eyngor et al, 2004). The selective pressure of different vaccine strategies in countries with a long history of lactococcosis has been also hypothesized to have caused the evolution of an ancestral common lineage into two different ones (Ravelo et al, 2003).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…There are eight recognized Lactococcus species and subspecies (1 (15)(16)(17). Increasing rates of infection with rising water temperatures (>16 ) typically during summer months has also been reported (15 …”
Section: Produced Lactic Acid From the Fermentation Of Carbohydrates mentioning
confidence: 99%